Electrochemically stable and ultrathin polymer-based solid electrolytes for dendrite-free all-solid-state lithium-metal batteries - Fenghua Yu; Yongbiao Mu; Meisheng Han; Jie Liu; Kunxiong Zheng; Zhiyu Zou; Hengyuan Hu; Quanyan Man; Wenjia Li; Lei Wei; Lin Zeng; Tianshou Zhao (Materials Futures)
Polymer-based composite solid electrolytes (PCSEs) are increasingly studied in all-solid-state lithium-metal batteries (ASSLMBs) due to the combined advantages of better flexibility of polymer and higher ion conductivity of ceramic electrolytes. However, most reported PCSEs are overly thick, increasing internal resistances. Besides, the poor stability at the Li metal–electrolyte interfaces often leads to severe lithium dendrite formation and reduced cycling stability. Here, we fabricate an ultrathin PCSE with a thickness of 12.4 μ m, incorporating polyacrylonitrile (PAN) nanofibers as the structural matrix, and a filler with polyethylene oxide and Li _6.5 La _3 Zr _1.5 Ta _0.5 O _12 (LLZTO). Due to the formation of the LiCN layer on the surface of the lithium metal and the Li-ion transport pathways induced by the dehydrocyanation reaction at the LLZTO/PAN interfaces, the PCSE exhibits a high critical current density of 1.8 mA cm ^−2 and a low energy barrier of 0.278 eV for Li-ion transfer, accommodating the fast Li-ion migration to avoid Li-dendrite growth. In addition, the stable nitrile groups and the dehydrocyanation reaction ensure the electrochemical stability of the PCSE with a high oxidation voltage of 5.5 V and an exceptional cycling stability (2100 h) in Li||PCSE||Li symmetric cells. Additionally, the Li||PCSE||LiFePO _4 full cells demonstrate a high volumetric energy density of 338.3 Wh L ^−1 at 0.1 C and a robust stability over 100 cycles at 0.5 C. The study offers a new approach for fabricating ultrathin PCSEs and provides insights into the mechanisms of dendrite-free formation, guiding the development of high-performance PCSEs for ASSLMBs.